Immersion program in Lifestyle Medicine and its effects on cardiovascular risk factors: Programa de inmersión en Medicina del Estilo de Vida y sus efectos sobre los factores de riesgo cardiovasculares - Ballone, Abigail (2021)
Introduction: Cardiovascular diseases are the leading cause of death worldwide and are associated with increased morbidity and mortality by COVID-19. Lifestyle Medicine immersion programs consist of a residential internship that performs a multidisciplinary professional follow-up.  Objective: To evaluate the effect of the residential lifestyle medicine program on risk factors for cardiovascular disease: weight, blood pressure and glycemia. Methods: Longitudinal, comparative study, with intervention of a Lifestyle Medicine Program. Retrospective data from 2019-2021 of patients who had completed the intervention for 14 days were used. This consisted of a comprehensive follow-up: medical, nutritional, psychological, physical and spiritual of the patients. Results: Of the 53 patients evaluated, 26 underwent the intervention before the pandemic, who were hospitalized with the main reason for weight loss 34.62%. Of the patients who underwent the intervention within the pandemic (N=27), the main reason for hospitalization was for treatment of chronic diseases 33.33%. Glycemia: Initial M=186.64, SD=81.73; Final M=119.93, SD=35.02. Mean reduction of 66.71 mg/dl, statistically significant (t=4.3460, p=0.0008). SBP: Initial M=127.76, SD=16.36; Final M=115.21, SD=14.87. Mean reduction of 12.55 mmHg, statistically significant (t=4.7048, p=0.0001). Conclusions: The effect of the intervention was significant in the cardiovascular risk factors evaluated: weight, glycemia and systolic blood pressure. It was possible to reduce the risk factors for cardiovascular disease with intensive lifestyle changes. In times of pandemic, the relevance of lifestyle medicine intervention is emphasized.